A Thematic Analysis of Paternalistic Leadership - Baysak, Birol; Bilgeturk, Mahmut (CHIANG MAI UNIV, FAC SCIENCE, 2021)
This review article aims to examine studies about paternalistic leadership (PL) and present an overview of the literatures' themes. The study examined articles based on their types, practices, institutions, and country distribution. A total of 271 articles were determined suitable for review. Papers were coded sequentially, and subthemes were created inductively rather than by attempting to fit them into a preexisting coding framework. Based on thematic analysis, four key themes emerged: the individual, organizations, leaders, and others. Most of the studies reviewed were empirical and quantitative. As this review article contributes a review of the literature on PL and defines its four top thematic groups, it serves as a guide for future researchers studying PL.
Keywords: Paternalistic leadership; moral leadership; benevolent leadership; authoritarian leadership; MODERATING ROLE; MEDIATING ROLE; EMPLOYEE CREATIVITY; INNOVATIVE BEHAVIOR; JOB-PERFORMANCE; CHINESE; ORGANIZATIONS; CONTEXT; Social Sciences - Other Topics